The long-term effects of consecutive COVID-19 waves on mental health - Novotný, Jan Sebastian; Gonzalez-Rivas, Juan Pablo; Kunzová, Šárka; Skladaná, Mária; Pospíšilová, Anna; Bartošková, Anna; Vassilaki, Maria; Medina-Inojosa, Jose Ramon; Lopez-Jimenez, Francisco; Geda, Yonas Endale; Stokin, Gorazd Bernard (BJPsych open, 2023)
BACKGROUND: Although several studies have documented the impact of the COVID-19 pandemic on mental health, the long-term effects remain unclear. AIMS: To examine longitudinal changes in mental health before and during the consecutive COVID-19 waves in a well-established probability sample. METHOD: An online survey was completed by the participants of the COVID-19 add-on study at four time points: pre-COVID-19 period (2014-2015, n = 1823), first COVID-19 wave (April to May 2020, n = 788), second COVID-19 wave (August to October 2020, n = 532) and third COVID-19 wave (March to April 2021, n = 383). Data were collected via a set of validated instruments, and analysed with latent growth models. RESULTS: During the pandemic, we observed a significant increase in stress levels (standardised β = 0.473, P < 0.001) and depressive symptoms (standardised β = 1.284, P < 0.001). The rate of increase in depressive symptoms (std. covariance = 0.784, P = 0.014), but not in stress levels (std. covariance = 0.057, P = 0.743), was associated with the pre-pandemic mental health status of the participants. Further analysis showed that secondary stressors played a predominant role in the increase in mental health difficulties. The main secondary stressors were loneliness, negative emotionality associated with the perception of COVID-19 disease, lack of resilience, female gender and younger age. CONCLUSIONS: The surge in stress levels and depressive symptoms persisted across all three consecutive COVID-19 waves. This persistence is attributable to the effects of secondary stressors, and particularly to the status of mental health before the COVID-19 pandemic. Our findings reveal mechanisms underlying the surge in mental health difficulties during the COVID-19 waves, with direct implications for strategies promoting mental health during pandemics.